Ortner's Syndrome in the Modern Era: A Series of 7 Cases - AKM Monwarul Islam; Ishrat Jahan Shimu; Kaniz Fatema Ananya; Rezvey Sultana; Saima Alam (Global Journal of Rare Diseases - Peertechz Publications, 2018)
Ortner syndrome (OS) is a rare condition characterized by hoarseness of voice in association with a cardiovascular disease. Mitral stenosis is a well-recognized cause; however, because of control of rheumatic fever and rheumatic heart disease in many parts of the world, there may be a shift of the underlying aetiology to other cardiac and non-cardiac conditions. Aortic diseases and pericardial effusion as the cause of OS, are being increasingly recognized. Here, 7 cases of OS have been presented, with special attention to their clinical presentation, underlying pathology, diagnostic work-up, treatment offered and the prognosis observed. Three cases expired, 2 cases were managed successfully, while 2 cases are waiting for surgery. In all cases, hoarseness of voice did not improve. OS should be a differential diagnosis while dealing with a patient with otherwise unexplained hoarseness of voice.